Combining the serum pepsinogen level and Helicobacter pylori antibody test for predicting the histology of gastric neoplasm. Issue 6 (June 2014) - Choi, Hong Seok; Lee, Sun‐Young; Kim, Jeong Hwan; Sung, In‐Kyung; Park, Hyung Seok; Shim, Chan Sup; Jin, Choon Jo
<x xml:space="preserve">Abstract</x> Objective To determine whether the combination test of serum pepsinogen (PG) levels and Helicobacter pylori (H. pylori) antibody was effective for predicting the incidence and histology of gastric neoplasms. Methods This study included asymptomatic Korean adults who underwent esophagogastroduodenoscopy with blood tests for PG levels and H. pylori immunoglobulin G antibody test on the same day. Participants with extragastric malignancy, history of H. pylori eradication or gastric neoplasms, or recent antacid medication were excluded. Gastric atrophy was defined as a serum PG I/II ratio ≤3.0 and PG I ≤70 ng/mL. The participants were classified into four groups according to the presence (+) or absence (−) of gastric atrophy and H. pylori infection. Results Of the 3328 included participants, 17 were incidentally diagnosed as having either gastric adenoma or carcinoma. The incidence of gastric neoplasm was highest in the gastric atrophy (+)/H. pylori (−) group (4.17%; OR 25.8, P = 0.009), but the neoplasm exhibited the least advanced histology. The gastric atrophy (−)/H. pylori (−) group exhibited the lowest incidence of gastric neoplasm (0.17%) but the most advanced histology. Conclusion A combination of serum PG levels and H. pylori antibody test is useful for detecting gastric neoplasms based on the slow gastric carcinogenesis pathway progressing from gastric adenoma to Lauren's intestinal‐type gastric cancer, but not for those with advanced histology such as Lauren's diffuse‐type gastric cancer.